1996
DOI: 10.1111/j.1365-2788.1996.tb00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular defects in children and adolescents with severe mental deficiency

Abstract: To assess the need for eye care in children and adolescents with severe mental deficiency, a cross-sectional study of the prevalence and causes of ocular defects amongst these individuals was conducted. Two hundred and sixty residents in a mental handicap unit were examined from January 1992 to June 1993. It was found that there was an unusually high prevalence of severe visual impairment (25%), refractive errors (24%), squint (8%) and a number of organic ocular diseases (8%). All the patients studied were non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 14 publications
1
28
2
Order By: Relevance
“…Levy [1984] found higher percentages of hyperopia/astigmatism than myopia/astigmatism among Canadian adults with ID (23 and 13%, respectively). In contrast to most Western studies indicating that hyperopia is more prevalent than myopia among individuals with ID, Kwok et al [1996] found myopic and hypermetropic astigmatisms to be equally prevalent in Hong Kong.…”
contrasting
confidence: 46%
See 1 more Smart Citation
“…Levy [1984] found higher percentages of hyperopia/astigmatism than myopia/astigmatism among Canadian adults with ID (23 and 13%, respectively). In contrast to most Western studies indicating that hyperopia is more prevalent than myopia among individuals with ID, Kwok et al [1996] found myopic and hypermetropic astigmatisms to be equally prevalent in Hong Kong.…”
contrasting
confidence: 46%
“…International research on specific subpopulations of those with ID, however, has found slightly lower prevalence estimates of those with refractive errors. For example, a Swedish study of institutionalized individuals with ID reported that 23% had a considerable refractive error in the best eye, and a Hong Kong study found 24% of individuals with profound ID [intelligence quotient (IQ) Ͻ 25] had refractive errors [Jacobson, 1988;Kwok et al, 1996].…”
mentioning
confidence: 99%
“…Refractive errors (24%), strabismus (8%), and a number of organic ocular diseases (8%) were also detected in one of these reports. 118 Supporting these findings is a class IV retrospective review that estimated the frequency of primary visual sensory impairment in children with global developmental delay to range between 20% and 50%. 114 There also appears to be an increased prevalence of additional visual developmental disability among individuals with syndromes featuring significant sensory impairment.…”
Section: Are Vision and Hearing Disorders Common In Children With Glomentioning
confidence: 72%
“…120 In one class III study of 260 children with severe global developmental delay in whom vision and audiologic screening were performed, 18% of children were found to be deaf. 118 Another class III study involving 96 children with global developmental delay and clinically suspected hearing loss found that 91% had hearing loss as detected by behavioral audiometry or brainstem auditory evoked response testing. 121 The feasibility of utilizing transient evoked otoacoustic emissions, compared to standard audiometry, to screen for hearing impairment in children has been demonstrated (class II study).…”
Section: Are Vision and Hearing Disorders Common In Children With Glomentioning
confidence: 99%
“…Correction of refractive errors has been found to bring significant improvement even in motor behaviours. 32 In a prospective study of the prevalence of vision disorders, other than refractive anomalies, the most prevalent conditions in the clinical paediatric population are binocular and accommodative disorders. 33 At initial assessment, binocular vision was reduced and absent in 9.7 and 4.2%, respectively, similar to previously reported.…”
Section: Discussionmentioning
confidence: 99%